Dai Multi-Competence: Implementation of Da'wah Bil-Hal For Preaching Activities in Rural Society Environments - Muhammad Umar Khadafi (ORASI: Jurnal Dakwah dan Komunikasi, 2025)
At this time, there are more and more challenges in da'wah activities. Da'wah is not enough through the pulpit and media sharing. People in rural and remote areas still have problems, including education and economic issues. Direct and intensive guidance from a da'i is very much needed by the community. This study aims to produce an applicable approach for da'wah activities in rural and remote communities in Indonesia. The research data was obtained through interviews and direct observation in the field. A descriptive qualitative research approach was used, with Miles and Huberman's analysis method. This research produced the concept of a multi-competent da'i, whose competencies include the following. First, religious competence, including the Quran, hadith and Islamic studies as the scientific basis that must be possessed. Second, social competencies include cupping therapy, ruqyah, and self-defence. Third, economic empowerment competencies include agriculture and animal husbandry. These findings imply that the activities of da'i must directly touch the community with various activities that must be mastered, not merely delivering religious messages to the community. More than that, a da'i must have complex competencies, especially since the target of these da'wah activities is the community in rural and remote areas or segments of society that are isolated from technology. This paper has limited scope, so further research is needed to provide more interesting and relevant studies related to da'wah bil-hal for rural communities in Indonesia.